Intercarotid artery distance in the pediatric population: Implications for endoscopic transsphenoidal approaches to the skull base. (January 2021) - Li, Lifeng; Carrau, Ricardo L.; Prevedello, Daniel M.; Yang, Bentao; Rowan, Nicholas; Han, Demin; London Jr., Nyall R.
Abstract: Objective: Comprehensive quantitative evaluation of the intercarotid artery distance (ICD) in the pediatric population has not been sufficiently explored. This study aims to measure the minimal ICDs at multiple levels of the skull base to assess changes in the ICD during development. Methods: Measurement of the ICDs between the paired paraclival, parasellar, and paraclinoid segments of the internal carotid artery (ICA) was performed on coronal MRI from 540 patients ranging from 0 to 17 years old (n = 30 for each age). Comparison of these indices in the very young (0–5 years, Group 1) and young (6–17 years, Group 2) patients, and assessment of the degree of sphenoid sinus pneumatization was employed. Results: The narrowest ICD was located at the paraclinoid ICAs in the vast majority of cases (89.44%). When comparing the ICDs in very young age patients with the ICDs of 17 years old subjects, a statistically significant difference was found at the paraclival (ages 0–5), parasellar (ages 0–2), and paraclinoid (ages 0–4) ICDs (p < 0.05). Comparison of the ICDs between the intergroups (Group 1 and 2) also demonstrated a statistically significant difference (p < 0.0001). Pneumatization of the sphenoid sinus was initially noted to start at 3 years of age, and there were no patients with a non-pneumatized sphenoid sinus identified after 7 years of age in our cohort. Conclusion: Measurement of ICDs at multiple levels provides a valuable reference for EEA procedures in the pediatric population. While the ICD may be largely stable in the pediatric population after 5 years of age, additional anatomic factors may restrict transsphenoidal access in very young patients (0–5 years).